MPFL Reconstruction Using Quadriceps Tendon Graft - Our Five Years Expirience - Marinkovic, Jugoslav; Radunovic, Aleksandar; Vranic, Vladimir; Stasa, Munitlak (International Journal of Orthopedics and Rehabilitation, 2020)
The primary traumatic luxation of the knee cup affects the general population with an incidence of 5.8 per 100,000 (3), while in the younger age group (10-17 years) it goes up to 29 per 100,000. Most patients will not have instability after non-operative treatment, while repeated luxation will occur in 15 to 44% of cases. The use of the quadriceps tendon for medial patelofemoral ligament (MPFL) reconstruction is a method described independently by Steensen et al. and Noyes and Albright. Today have more and more supporters because of their simplicity, minimal trauma and good postoperative results. Reconstruction of MPFL with quadriceps tendon (QT) for recurrent patellofemoral instability started in our Clinic in 2014. Indications for surgery were patients who have had clear clinical and radiological signs of instability, tibial tubercle-trochlear groove distance (TT-TG) < 20 mm, dysplastic trochlea grade A according to the Dejour classification. For clinical testing we used apprehension and Veselko’s test. In our clinic 22 patients were operated in past fifth years. This study shows result of 17 patients. We noticed a significant improvement in patients in daily activities (instability, swelling, pain, kneeling, squatting, climbing stairs). All patients had full range of motion after approximately 3 months. The initial Lyscholm score value was 69.2 ± 6.4 while after two years 88.3 ± 3,2. Our observation shows that MPFL reconstruction with quadriceps graft in short time follow-up in selected cases may have very satisfactory results. The method itself is simple, inexpensive, with small complication rate and with great patients satisfaction.